Sport Diplomacy as a Use of Soft Power : A Comparative Case Study Analysis - Horne, Eli (2018)
This thesis identifies how sports diplomacy is used to establish and repair relationships amongst nations. The purpose of this research is to see how this modern form of diplomacy is conducted in the efforts of enhancing foreign relations between nations, where other approaches have previously lacked certain characteristics to break barriers in bringing nations together. The use of liberal international relations theory – in association with supranational institutions as governing bodies in the realm of sports – and soft power – as a trait of cultural connections between the nations – are used to draw linkages in establishing a concrete answer of the research question. The methodology allocated to answer this question is a comparative case study analysis. This research format will be conducted with the study of four cases, investigating aspects and comparing the results of how sports diplomacy was utilized. All examples produce different outcomes or practices of sports diplomacy. The conclusions made draw connections between the theoretical framework and different cases selected. These connections made show how sports diplomacy is operated to bring nations together through the practice of sports, with the outcome of improved relations. The objectives in the thesis are successfully answered. However, new questions have arisen with further analysis of the topic, questioning theoretical aspects and tactics used in the art of sports diplomacy.